Two C1-oxidizing lytic polysaccharide monooxygenases from Ceriporiopsis subvermispora enhance the saccharification of wheat straw by a commercial cellulase cocktail. (November 2021) - Long, Liangkun; Sun, Lu; Ding, Dafan; Chen, Kaixiang; Lin, Qunying; Ding, Shaojun
Graphical abstract: Highlights: Two new LPMOs of AA9 family from C. subvermispora were functionally identified. The two LPMOs specifically oxidized the C1 carbon atom of glucose unit in cellulose. The two enzymes stimulated the saccharification of wheat straw by a commercial cellulase. Abstract: Two genes encoding lytic polysaccharide monooxygenases (LPMOs) Cs LPMO9A and Cs LPMO9B were cloned from the white-rot fungus Ceriporiopsis subvermispora and successfully expressed in Komagataella phaffii . The oxidative degradation of phosphoric acid swollen cellulose by the LPMOs was conducted using ascorbic acid as an electron donor. Analysis with high performance anion-exchange chromatography and matrix assisted laser desorption/ionization-time-of-flight mass spectrometry indicated that the two enzymes cleaved the polysaccharides by oxidization of the C1 carbon atom of the glucose unit. Synergistic effects between Cs LPMO9A or Cs LPMO9B and a commercial cellulase cocktail from Trichoderma reesei were observed in the saccharification of delignified wheat straw. The amounts of glucose, cellobiose and xylose released from the substrate by the combined enzymes were increased by 83 %, 16 % and 47 % (for Cs LPMO9A), or 79 %, 52 % and 81 % (for Cs LPMO9B), compared to the cellulase alone, respectively. The two new enzymes displayed promising potential in industrial bioconversion of lignocellulosic biomass.